Integration of Spatial and Non Spatial Databases for Watershed Management - S. Dash, Shefali; Nagubhushanam, G.; Vaish, Parabhant K.; Pathak, Ajay; Roy, Ajay (Journal of Soil and Water Conservation, 2022)
Watershed, by simple definition, is a geo-hydrological unit or piece of land that drains at a common point In view of the microlevel planning approach, it has been proposed to consider the watershed boundary as the unit of planning.